Investigation of the Effects of Different Polishing Methods on Tooth Surfaces in Smokers: An In Vitro Study - Ezgi Gurbuz; Mehmet Meric Ersoz; Feridun Karakoc; Hasan Hatipoglu (Galician Medical Journal, 2025)
Introduction. This in vitro study aimed to compare the enamel and root surfaces of teeth between smokers and non-smokers after scaling with hand instruments and to evaluate surface characteristics of smokers’ teeth after applying different polishing methods.